Initial testing (stage 1) of tazemetostat (EPZ‐6438), a novel EZH2 inhibitor, by the Pediatric Preclinical Testing Program. Issue 3 (24th August 2016) - Kurmasheva, Raushan T.; Sammons, Melissa; Favours, Edward; Wu, Jianwrong; Kurmashev, Dias; Cosmopoulos, Katherine; Keilhack, Heike; Klaus, Christine R.; Houghton, Peter J.; Smith, Malcolm A.
Abstract: Background: Tazemetostat (EPZ‐6438) is a selective inhibitor of the histone methyltransferase EZH2 and currently in clinical development for non‐Hodgkin lymphoma and genetically defined tumors. Procedures: Tazemetostat was tested against the Pediatric Preclinical Testing Program (PPTP) solid tumor xenografts using a dose of 400 mg/kg administered twice daily by oral gavage for 28 days. H3K27me3:H3 ratios were determined in control and treated tumors. Results: Tazemetostat induced significant differences in event‐free survival (EFS) distribution compared with control in nine of 30 (30%) of the xenografts studied. Significant differences in EFS distribution were observed in five of seven (71%) rhabdoid tumor xenograft lines compared with four of 23 (17%) nonrhabdoid xenograft lines (chi‐square [χ 2 ] test P = 0.006). Tazemetostat induced tumor growth inhibition meeting criteria for intermediate and high EFS treated‐to‐control (T/C) activity in two of 25 (8%) and one of 25 (4%) xenografts, respectively. Intermediate and high activity for the EFS T/C metric was observed exclusively among rhabdoid tumor xenografts (three of five rhabdoid tumor vs 0 of 22 nonrhabdoid tumors (χ² test P < 0.001). One rhabdoid tumor xenograft (G401) showed stable disease. For one rhabdoid tumor (G401), delayed tumor regression to tazemetostat was noted following 1 week of tumor growth. Tazemetostat induced significant reduction of H3K27me3 levels in the majority of tumors compared with controls. Conclusions: Tazemetostat demonstrated significant antitumor activity in rhabdoid tumor models but showed no consistent activity against any other histology. Tazemetostat reduced H3K27me3 levels irrespective of tumor response. Further preclinical testing to evaluate tazemetostat in combination with other anticancer agents is warranted.